The Form of the Language Politeness of State Officials in Q and A Metro TV Talkshow: Pragmatic Analysis (Universitas Negeri Semarang, 2019)
Language is human nature, meaning that language as a means of verbal communication is only possessed by humans. The politeness of speech spoken by state officials in Q and A Metro TV talkshow is an interesting phenomenon to be studied from a pragmatic perspective since social and verbal interactions of state officials will appear as natural as possible when state officials communicate with hosts and panelists. This study analyzed the forms and types of violations and the obedience of Leech maxim politeness of state officials in Q and A Metro TV Talk Show. The study was analyzed using a pragmatic and descriptive qualitative approach. The data was collected by listening and note-taking. The data analysis techniques in this study was normative technique. The obedience with the principle of politeness can be found in the maxim of generosity, the maxim of acceptance, the maxim of modesty, the maxim of approval, and the maxim of sympathy. Violations on the principle of politeness are on the maxim of judgement, maxim of generosity, maxim of courtesy, maxim of modesty, and maxim of approval. The benefit of this study is to provide an understanding of the politeness of the speeches of state officials in Q and A Metro TV Talk Show.